The Use of Standards in HELIO - KENNY, EAMONN; COGHLAN, BRIAN (My University, 2012)
HELIO [8] is a project funded under the FP7 program for the discovery and analysis of data for heliophysics. During its development, standards and common frameworks were adopted in three main areas of the project: query services, processing services, and the security infrastructure. After a first, proprietary implementation of the security service, it was suggested moving it to a standard security framework to simplify the enforcement of security on the different sites. As the HELIO front end is built with Spring and the TAVERNA server (HELIO workflow engine) has a security framework compatible with Spring, it has been decided to move the CIS in Spring security [2]. HELIO has two different processing services: one is a generic processing service called HELIO Processing Services (HPS), the other is called Context Service (CTX) and it runs specific IDL procedures. The CTX implements the UWS [4] interface from the IVOA [5], a standard interface for job submission used in the helio and astro-physics community. In its final release, the HPS will expose an UWS compliant interface. Finally, some of the HELIO services perform queries, to simplify the implementation and usage of this services a single query interface (the HELIO Query Interface) has been designed for all these services. The use of these solutions for security, execution, and query allows for easier implementation of the original HELIO architecture and for a simpler deployment of the services
PUBLISHED
Keywords: Heliophysics; Smart & Sustainable Planet